2013
DOI: 10.1088/0029-5515/53/7/073051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between MHD events, magnetic resonances and transport barriers in TJ-II plasmas

Abstract: In the TJ-II stellarator, a medium-sized heliac device that operates at high rotational transform and low magnetic shear, a close relationship is identified between abrupt changes in transport (in the form of radial fluxes, edge or internal transport barriers), broadband magnetohydrodynamic (MHD) events and the location of magnetic resonances. The observations are based on the local behaviour of plasma radiation. Phenomena that appear like sawteeth and crashes in tokamaks are found in practically all kinds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…At present, the rotational transform profiles of a given experiment have to be inferred from the theoretical expectations (e.g. vacuum rotational profiles, current diffusion) and MHD activity as measured with magnetic and radiation diagnostics [58] .…”
Section: Feedback Options For Magnetic Configuration Sweep Controlmentioning
confidence: 99%
“…At present, the rotational transform profiles of a given experiment have to be inferred from the theoretical expectations (e.g. vacuum rotational profiles, current diffusion) and MHD activity as measured with magnetic and radiation diagnostics [58] .…”
Section: Feedback Options For Magnetic Configuration Sweep Controlmentioning
confidence: 99%
“…However, the stability of ITB is a critical concern. A continuous growth of the m/n = 1/1 mode can lead to the collapse of ITB, especially when the minimum safety factor, q min , approaches to unity [5,6]. Furthermore, three-dimensional nonlinear magnetohydrodynamic (MHD) simulations within tokamak geometry suggest that an increase in β p might mitigate the saturation amplitude of such infernal-type m/n = 1/1 modes [7].…”
Section: Introductionmentioning
confidence: 99%
“…ELM‐like events have also been observed in the heliotron LHD and the heliac TJ‐II. In the case of TJ‐II, such events are first seen in low‐density electron cyclotron resonance heated (ECRH) plasmas (average electron density n e < 10 19 m −3 ) and later in NBI heated plasmas (1.5 × 10 19 m −3 < n e < 4 × 10 19 m −3 ) . For both heating modes in TJ‐II, it was found that the instability pivotal position is located near low‐order resonant (rational) magnetic surfaces, typically around iota central values of ι ≈ 1.5 (where iota, ι , is value of the rotational transform, which is the inverse of the safety factor, q , in tokamaks).…”
Section: Introductionmentioning
confidence: 99%